2018
DOI: 10.1007/s00402-018-2923-z
|View full text |Cite
|
Sign up to set email alerts
|

Femoral tunnel widening is associated with tunnel malposition but not with clinical failure after medial patellofemoral ligament reconstruction with a free gracilis tendon graft

Abstract: Tunnel enlargement after MPFL reconstruction with a free gracilis tendon graft seems to be connected to mechanical overload due to a proximal malposition of the femoral tunnel. Interestingly, this did not influence clinical outcome as patients with tunnel enlargement showed better Kujala and IKDC scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…These findings indicate that it is not a single but rather a combination of conditions that underly the indication for a two-staged procedure in the majority of patients. The association of ligament malposition and tunnel widening is a phenomenon also observed in other studies [16,18,22,33]. Concerning the extend of tunnel malpositioning and the distribution of tunnel widenings, no differences were noted between the two groups (Figs.…”
Section: Discussionsupporting
confidence: 83%
“…These findings indicate that it is not a single but rather a combination of conditions that underly the indication for a two-staged procedure in the majority of patients. The association of ligament malposition and tunnel widening is a phenomenon also observed in other studies [16,18,22,33]. Concerning the extend of tunnel malpositioning and the distribution of tunnel widenings, no differences were noted between the two groups (Figs.…”
Section: Discussionsupporting
confidence: 83%
“…43,58 However, only few reports have described the potential causes of postoperative complications in the eye of femoral tunnel placement. 10,13,52,56,57 In the case series by Camp et al, 13 nonanatomic femoral positioning of the MPFL was found to be the only significant risk factor for failure. Sanchis-Alfonso et al 52 found that failed MPFL reconstruction was significantly anteriorly when compared with clinically successful reconstruction.…”
Section: Discussionmentioning
confidence: 92%
“…11 In other clinical studies, malpositioned femoral tunnels have been associated with postoperative complications, 81 recurrent patellar instability or patellofemoral pain, 37,59 and tunnel widening. 69 Despite knowledge about the importance of anatomic tunnel placement, the rate of nonanatomic placement is reported to be as high as 60%. 52,72 The femoral MPFL insertion site can be identified fluoroscopically through use of radiographic landmarks on a true lateral knee radiograph or by palpation of anatomic landmarks.…”
Section: Discussionmentioning
confidence: 99%